The Impact of a Youtube-Assisted Contextual-Based E-Module on EFL Learners’ Speaking Skills - Ilyas, Muhammad; Putri, Miranti Eka (JOLLT Journal of Languages and Language Teaching, 2025)
The objective of this study is to create a YouTube-assisted contextual-based e-module that functions as a pedagogical component that can basically be applied to improve speaking skills. Contextual learning provides tools for teaching that can be developed and designed in an innovative way to increase learning for all students. This contextual-based e-module incorporates YouTube as an integrated resource, offering lecturers a valuable tool to enhance their teaching with a wide range of engaging and relevant content. The videos available on YouTube align well with the instructional material, providing both interesting and practical support to enrich the learning experience. This study employed the Borg and Gall research and development (R&D) model, which consists of six stages: needs analysis, objective planning, and development of the initial product, preliminary field testing, main product revision, and main field testing. A total of 50 students from the English Language Education Study Program at the Universitas Islam Riau, who were enrolled in the Speaking for General Communication course, participated in the study. This research used a mixed-methods approach, utilizing tests, questionnaires, and interview guides as data collection instruments. The results show that students responded positively to the use of the contextual-based e-module, which effectively improved their speaking skills. The e-module was also found to be practical, engaging, and supportive of independent learning. Importantly, the findings indicate that the module fosters greater student responsibility and autonomy in their learning. These results have practical implications for classroom instruction, suggesting that the integration of multimedia and contextual strategies can significantly enhance speaking pedagogy in higher education.